Nieuczciwe praktyki na rynku ubezpieczeniowym – klauzule abuzywne - Wieteska, Stanisław (Annales. Etyka w Życiu Gospodarczym, 2011)
In market economy to protect consumers’ rights in an extremely important insure. This also applies to the insurance market generally understood as issues related to the conclusion and execution of insurance contracts. Insured is exposed to many dangers, is weaker in the insurance market, because insurance as professionals may impose their conditions Convenient for the transaction. This article aims to identify the market practices by means of the unfair terms used by insurance companies. The article gives examples of unfair terms and points the consequences of their use.